2020
DOI: 10.1111/aos.14731
|View full text |Cite
|
Sign up to set email alerts
|

The impact of advanced age‐related macular degeneration on the National Eye Institute’s Visual Function Questionnaire‐25

Abstract: Purpose To assess visual function among patients diagnosed with age‐related macular degeneration (AMD) by stage of disease and laterality. Methods This is a cross‐sectional cohort study of 739 AMD patients and their responses to the National Eye Institute Visual Function Questionnaire‐25 (NEI VFQ‐25) at time of study enrolment. Patients with AMD were categorized into Early/Intermediate AMD and three groups of advanced AMD: (i) neovascular AMD (NV), (ii) geographic atrophy (GA) and (iii) Both Advanced forms. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
3
11
0
Order By: Relevance
“…The NEI-VFQ-25 assesses the self-reported, vision-targeted health status of people with chronic eye diseases. The NEI-VFQ-25 has been used to evaluate the subjective visual function and health-related quality of life between people free of eye disease and those with eye disease and detect changes after various intraocular procedures such as contact lens wearing or surgery [ 7 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The NEI-VFQ-25 contains 25 questions: general health, general vision, ocular pain, distance, near tasks, dependency on others, role limitation, mental health, social function, driving, peripheral vision, and color vision difficulty.…”
Section: Methodsmentioning
confidence: 99%
“…The NEI-VFQ-25 assesses the self-reported, vision-targeted health status of people with chronic eye diseases. The NEI-VFQ-25 has been used to evaluate the subjective visual function and health-related quality of life between people free of eye disease and those with eye disease and detect changes after various intraocular procedures such as contact lens wearing or surgery [ 7 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The NEI-VFQ-25 contains 25 questions: general health, general vision, ocular pain, distance, near tasks, dependency on others, role limitation, mental health, social function, driving, peripheral vision, and color vision difficulty.…”
Section: Methodsmentioning
confidence: 99%
“…Eyesight was reported as the most common reason for giving up driving in the GA group (81%) Patients with GA experience a poorer level of vision-related function and QOL than controls (their peers), especially in relation to driving Patnaik et al (2019) 40 US Cross-sectional study to measure VRQOL in patients with AMD (including GA) n=594 patients Patient categories: Early/intermediate AMD (n=207) Advanced nAMD (n=113) GA (n=95) Advanced nAMD in one eye and any-stage dry AMD in the other (both) (n=179) Controls (n=306) NEI VFQ-25 Composite scores were highest in patients with early/intermediate dry AMD (90.2), followed by controls (83.1), patients with both (81.7), GA (77.0), and advanced nAMD (72.1) had the lowest overall mean scores Typically, patients with early/intermediate AMD and controls had higher scores compared with the three advanced AMD groups, particularly nAMD and GA The greatest differences between groups were seen in subscales of mental health, role limitations, dependency, and driving. Lower discrepancies were observed in subscales of general health, general vision, social functioning, color vision, and peripheral vision Composite scores for patients with GA and advanced nAMD were much lower (worse) than for patients with earlier disease Patnaik et al (2020) 20 US Cross-sectional study to measure visual function and VRQOL in patients with AMD (including GA) N=739 Patient categories: Early/intermediate AMD (n=294) Advanced nAMD (n=168) nAMD with GA (n=162) GA (n=115) Patients were stratified into unilateral and bilateral disease NEI VFQ-25 Composite scores were highest in patients with early/intermediate AMD and lowest in patients with bilateral disease that included GA In general, this pattern of scores persisted across subscales The lowest score was for driving in the group of patients with bilateral advanced disease that included GA Large differences in visual function were seen across different AMD groups and number of eyes affected with AMD Patients with bilateral disease that included GA had the lowest scores for visual functioning and VRQOL Singh et al (2019) 5 US Cross-sectional qualitative study to understand the burden of illness of GA from patient, caregiver, and eye care professional perspectives Patients with symptomatic GA (n=8), their caregivers (n=6), and eye care professionals (n=5) Semi-structured interview The following areas were affected: Patients: Social and psychological factors, helplessness, impact on sports/hobbies, meals or food preparation, religious activities, and long-distance travel. Stopping driving or changi...…”
Section: Resultsmentioning
confidence: 95%
“…Quality of life in patients with GA, as assessed by the NEI VFQ-25, was shown in a cross-sectional US study to be worse than that in patients with early/intermediate AMD and nAMD. 20 A study of 739 patients with AMD showed that mean composite scores were highest among early/intermediate patients (89.9) and lowest for the groups with bilateral GA (71.3) and bilateral GA plus nAMD (68.5). Overall, patients with bilateral disease consistently had lower mean scores than their unilateral counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…The extent of the visual impairment also limits the intervention outcomes. Patnaik et al [50] reported lower NEI-VFQ 25 scores among AMD patients with GA compared to neovascular AMD. In our study, the area of the GA was closely related to the VRQoL improvement for near activities.…”
Section: Discussionmentioning
confidence: 99%